Mitigating Adolescent Mythomania through Kindness-Based Pedagogy: Lessons Learned from Rural School - Umar Manshur; Baharun, Hasan; Lailis Zakiyah; Zohaib Hassan Sain; M. Aqil Fahmi Sanjani (Cendekia: Kependidikan dan Kemasyarakatan, 2025)
Mythomanic behavior among adolescents is a serious issue in the educational world because it is often perceived as being overcome solely through rewards and punishments. This research aims to understand how kindness-based pedagogy can be used to reduce mythomanic behavior in adolescents, particularly at Miftahul Ulum Islamic High School, a school located in a rural area with a strong religious background. This study employed a qualitative method with a case study design, utilizing data sources that included students, teachers, and school documents. Data were collected through in-depth interviews, participatory observations, and documentation. Analysis is carried out through reduction, grouping, and narrative interpretation. The results show that five kindness strategies, such as empathetic listening, loving correction, exemplary kindness, peer support through kindness circles, and reflective practice with gratitude and kindness journals, are effective in creating a safe emotional atmosphere, fostering lies, and reducing students' propensity to lie. This research contributes to the development of humanist pedagogical literature by providing a more empathetic, relevant, and sustainable approach compared to traditional models.